2018
DOI: 10.1007/s12594-018-1098-0
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Characterization and Controlling Factors of Chemical Composition of Spring Water in a Part of Eastern Himalaya

Abstract: This paper focuses on the suitability of spring water for drinking and irrigation purposes in a part of eastern Himalaya, south Sikkim. There are many anthropogenic and geogenic factors contributing as a source of major cations and anions in the spring water. The spring water chemistry show a variation in EC, pH, TDS, Temperature, Na+, K+, Mg2+, Ca2+, Fe2+, Pb, Mn, Cu, HCO3−, Cl−, PO43−, NO3−, F− and SO42−. Mainly two types of water quality indexing has been used, one for suitability of spring water for drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Silicate (feldspar) weathering is a primary geochemical process controlling the major ion chemistry of groundwater (especially in igneous aquifers) and surface waters (Mackenzie and Garrels 1965;Dehnavi et al 2011;Vishwakarma et al 2018;Atkinson 2019). Specifically, silicate-rock weathering increases the concentration of HCO 3 in groundwater in accordance with (Dehnavi et al 2011) Eq.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Silicate (feldspar) weathering is a primary geochemical process controlling the major ion chemistry of groundwater (especially in igneous aquifers) and surface waters (Mackenzie and Garrels 1965;Dehnavi et al 2011;Vishwakarma et al 2018;Atkinson 2019). Specifically, silicate-rock weathering increases the concentration of HCO 3 in groundwater in accordance with (Dehnavi et al 2011) Eq.…”
Section: Resultsmentioning
confidence: 69%
“…Specifically, silicate-rock weathering increases the concentration of HCO 3 in groundwater in accordance with (Dehnavi et al 2011) Eq. (1) Numerous researchers have found that in the (Ca + Mg) (y axis) versus (HCO 3 + SO 4 ) scatter diagram, the ionic concentrations plotting above the 1:1 equiline result primarily from carbonate (calcite and dolomite) weathering and dissolution and/or from reverse ion exchange (Datta and Tyagi 1996;Gomaa et al 2013;Vishwakarma et al 2018;Atkinson 2019), whereas those falling along the equiline are attributable to carbonate (calcite and dolomite) and sulfate mineral (e.g., gypsum, anhydrite) dissolution. Sample analyses that plot below the 1:1 line reflect silicate (feldspar) weathering/dissolution as the dominant process, or ion exchange is a second potential geochemical process.…”
Section: Resultsmentioning
confidence: 99%
“…The values found above 0.5 have been highlighted and considered for the relationship study. If the correlation coefficient is between 0.5 and 0.8, a moderate relationship was considered and above 0.8, a strong relationship was considered (Vishwakarma et al, 2019). It is clear from the results that the TSS was negatively correlated with all variables and was not significantly correlated with any of the parameters in all seasons.…”
Section: Correlation Matrix Analysismentioning
confidence: 94%
“…The concentration levels of TSS were observed at high levels in all the peripheral rivers of Dhaka under assessment (Figure 7). Chemical oxygen demand (COD) is very useful in assessing the resistance of industrial waste and sewage to contamination and the quantity of oxygen required to oxidize organic and inorganic materials in a sample [66]. The COD levels in Dhaleshwari varied between 121.2 and 935 mg/L (Figure 8).…”
Section: Assessment Of Physicochemical Parameters Of Surface Watermentioning
confidence: 99%